2015
DOI: 10.1038/cddis.2015.334
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-bound and soluble Fas ligands have opposite functions in photoreceptor cell death following separation from the retinal pigment epithelium

Abstract: Fas ligand (FasL) triggers apoptosis of Fas-positive cells, and previous reports described FasL-induced cell death of Fas-positive photoreceptors following a retinal detachment. However, as FasL exists in membrane-bound (mFasL) and soluble (sFasL) forms, and is expressed on resident microglia and infiltrating monocyte/macrophages, the current study examined the relative contribution of mFasL and sFasL to photoreceptor cell death after induction of experimental retinal detachment in wild-type, knockout (FasL−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 50 publications
0
39
2
Order By: Relevance
“…We also assessed for the activation of microglia and or infiltration of macrophages, which is often associated with outer retinal injury and activation of Fas-mediated cell death. 8,24,25 We observed that exposure to NaIO3 resulted in more Iba1-positive cells in retina flat mounts, and that this was significantly reduced by Met12- as compared to mMet12-treated eyes (Fig. 4B).…”
Section: Resultsmentioning
confidence: 82%
“…We also assessed for the activation of microglia and or infiltration of macrophages, which is often associated with outer retinal injury and activation of Fas-mediated cell death. 8,24,25 We observed that exposure to NaIO3 resulted in more Iba1-positive cells in retina flat mounts, and that this was significantly reduced by Met12- as compared to mMet12-treated eyes (Fig. 4B).…”
Section: Resultsmentioning
confidence: 82%
“…Exactly how the balance between sFasL and mFasL shifts during diseases such as glaucoma is unclear, but our data demonstrate that mFasL is definitely the pathogenic isoform. We have explored the role of mFasL vs sFasL in gene-targeted ΔCS mice where the FasL cleavage site has been mutated and can no longer be cleaved by metalloproteinases (27, 67). In ΔCS mice, total FasL expression is controlled by the endogenous FasL promoter as in WT mice, but in ΔCS mice, cells that normally express FasL can only make mFasL and not sFasL.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, using the retinal detachment model, we found upregulation of expression and phosphorylation of RIPK along with activation of caspases ( Figure 3 ). 160 , 167 , 172 , 173 When we tried to inhibit RIPK or caspases in isolation, no major effect on photoreceptor loss was observed. 167 In contrast, combined treatment led to significant rescue.…”
Section: Future Treatments—neuroprotectionmentioning
confidence: 99%